(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2021)
This paper aims to evaluate some stylistic elements in the Tarquinian funerary painting and architecture diffused in the areas of the Mediterranean and Black Sea during the Classic and Hellenistic era and to discuss the potential connection between the Etruscan city and these areas. The study of the Tarquinian painted tombs enables to emphasise certain peculiar features and to reconsider the role and the extent that the city assumes in the Hellenistic scenery, the reception, the assimilation of the change and the innovations concerning the painting techniques, the colours, the iconography and the beliefs derived from the Greek cultural areas. Also, in the Tarquinian area the Grotte Scalina tomb is enlightening for the architecture, whose characteristics refer to the Hellenistic palaces.